1979
DOI: 10.1037/0022-0663.71.5.646
|View full text |Cite
|
Sign up to set email alerts
|

Age, sex, and attractiveness as factors in student ratings of teachers: A developmental study.

Abstract: Black-and-white photographs of teachers, controlled for race, age, sex, and attractiveness, were rated on seven factors of teacher performance by students in Grades 2,5,7,11, and 13. Across all developmental levels and on all factors, ratings of unattractive teachers tended to be lower. At all developmental levels, older teachers tended to receive lower ratings than younger teachers. Sex of the teacher appeared to be a more influential factor at Grades 11 and 13. Interactions showed that unattractive middle-ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
5

Year Published

1988
1988
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 18 publications
0
26
0
5
Order By: Relevance
“…The first conducted by Chaikin, Gillen, E>erlega, Heinen & Wilson (1978), found that a teacher's attractiveness level influenced student ratings of competency, ability to stimulate students, and ability to motivate students. Goebel & Cashen's (1979) study added the dimension of ethnicity. One hundred and fifty subjects evaluated specific dimensions of a teacher's performance.…”
Section: Attractiveness and Expected Achievementmentioning
confidence: 99%
“…The first conducted by Chaikin, Gillen, E>erlega, Heinen & Wilson (1978), found that a teacher's attractiveness level influenced student ratings of competency, ability to stimulate students, and ability to motivate students. Goebel & Cashen's (1979) study added the dimension of ethnicity. One hundred and fifty subjects evaluated specific dimensions of a teacher's performance.…”
Section: Attractiveness and Expected Achievementmentioning
confidence: 99%
“…An older study, conducted by Goebel/Cashen (1979) also suggested that attractive lecturers receive better teaching evaluations. However, to the best of our knowledge, possible relations between research performance and academics' physical appearance have not been analysed yet.…”
Section: Introductionmentioning
confidence: 99%
“…En effet, les résultats laisseraient à penser que les élèves auraient des attitudes plus positives envers les enseignants jeunes (à = 10,54; s = 0,95) et d'âge moyen (à = 10,33; s = 1,20) et moins positives envers les enseignants plus âgés (à = 9,53; s = 1,77). Cette tendance rejoint les résultats obtenus par Goebel et Cashen (1979) qui montrent que l'âge de l'enseignant joue un rôle important dans la perception des élè-ves, sauf si ceux-ci sont jeunes.…”
Section: Présentation Et Discussion Des Résultatsunclassified
“…Goebel et Cashen (1979), Hickson, Handley et Thomson (1978), Fox, Peck, Blasstein et Blasstein (1983), Le Roy (1987), Luce et Hoge (1978, dans Pellerin, 1989, Pritchett et Willower (1975) ont examiné les rapports pouvant exister entre des caractéristiques de l'enseignant, tels l'attrait, le sexe, l'âge, la personnalité, l'habileté à enseigner ou le comportement, et les perceptions qu'en ont les élèves et les attitudes qu'ils nourrissent à son égard. Il ressort de ces travaux que les relations les plus importantes impliquent les facteurs «at-trait» et «âge» de l'enseignant.…”
Section: Les Variables Qui Influencent Les Attitudes Des éLèves Enverunclassified